2006
DOI: 10.3892/ijo.28.6.1531
|View full text |Cite
|
Sign up to set email alerts
|

Effective silencing of EGFR with RNAi demonstrates non-EGFR dependent proliferation of glioma cells

Abstract: Abstract. The epidermal growth factor receptor (EGFR, ErbB1) is frequently dysregulated in a variety of solid human tumors, including malignant glioma. EGFR expression has been associated with disease progression, resistance to standard therapies and poor survival. The application of small interfering RNAs (siRNAs) has become an effective and highly specific tool to modulate gene expression, and a wide range of oncogenes have been silenced successfully. Here we show the siRNA-mediated down-regulation of EGFR i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
3
0

Year Published

2006
2006
2013
2013

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 40 publications
4
3
0
Order By: Relevance
“…Hegi et al showed that the tissue drug concentrations are increased and efficient EGFR dephosphorylation takes place both in vivo and in vitro , but the downstream pathway remains active. Persistent EGFR downstream signalling has also been reported by Hasselbalch et al on glioblastoma cell lines treated with cetuximab, an anti‐EGFR monoclonal antibody, and by Vollman et al using siRNAs. These findings suggest that EGFR downstream signalling is independent of receptor activation and that simultaneous downstream signals might co‐exist or be initiated as a response to EGFR blockade.…”
Section: Epidermal Growth Factor Receptor (Egfr)supporting
confidence: 57%
“…Hegi et al showed that the tissue drug concentrations are increased and efficient EGFR dephosphorylation takes place both in vivo and in vitro , but the downstream pathway remains active. Persistent EGFR downstream signalling has also been reported by Hasselbalch et al on glioblastoma cell lines treated with cetuximab, an anti‐EGFR monoclonal antibody, and by Vollman et al using siRNAs. These findings suggest that EGFR downstream signalling is independent of receptor activation and that simultaneous downstream signals might co‐exist or be initiated as a response to EGFR blockade.…”
Section: Epidermal Growth Factor Receptor (Egfr)supporting
confidence: 57%
“…In agreement with previous studies , the results of the present study also revealed that down‐regulation of EGFR did not reduce cell proliferation as significantly as β‐catenin inhibition from both the cell viability and clonogenic assays, which thereby resulted in a comparable inhibitory effect of targeting β‐catenin alone versus the combinatorial treatment. There have been conflicting reports in the literature regarding the therapeutic effect of targeting EGFR against GBM.…”
Section: Discussionsupporting
confidence: 93%
“…siRNA-mediated knockdown of Rictor was also previously reported to have no effect on cell proliferation, survival and invasion [71]. The absence of significant therapeutic effects associated with EGFR inhibition described here also correlates with results observed in the clinic [61], [74][76] using small molecule EGFR inhibitors, and in some pre-clinical GBM studies [77][79] using small molecule EGFR inhibitors or siRNA. More specifically, Fan et al reported that the EGFR inhibitor gefitinib or the pan-PI3K inhibitor LY294002 given as monotherapy had no impact on tumor burden in a GBM model, yet when these inhibitors were used in combination, they blocked tumor growth [78].…”
Section: Discussionsupporting
confidence: 86%